Code-based generalized signcryption scheme with multi-receiver - Yiliang HAN; Zhong WANG (Tongxin xuebao)
In order to solve the problem of secure transmission of messages with multiple receivers,a code-based generalized signcryption scheme with multi-receiver was designed.Firstly,a multi-encrypted McEliece scheme that can meet the security of IND-CCA2 was designed.Combined with the CFS signature scheme,the multi-receiver signcryption and generalized signcryption scheme based on code were designed.The security analysis shows that the multi-receiver generalized signcryption scheme can meet the security of IND-CCA2 in terms of confidentiality and can meet EUF-CMA security in terms of unforgeability.Compared with other similar multi-receiver signcryption schemes,the proposed scheme does not include exponential,bilinear pairing operations,etc.,and has high computational efficiency and the advantage of anti-quantum computing.Compared with the method of signing-then-encrypting method,the proposed scheme has the smaller private key and higher efficiency.